2005
DOI: 10.1021/je050347n
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of β-FeF3·3H2O in Mixtures of Nitric and Hydrofluoric Acid

Abstract: The solubility of β-FeF 3 ‚3H 2 O has been measured in solutions with different concentrations of nitric acid (0 to 7 m) and hydrofluoric acid (1 to 6 m) at the temperatures of (30, 40, and 50) °C. The total iron concentration at equilibrium was measured with inductively coupled plasma (ICP) spectroscopy. The solubility was evaluated in terms of the stepwise complexation of iron by fluoride ions at different ionic strength and temperature. The solubility of β-FeF 3 ‚3H 2 O increases with decreasing concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…When higher temperatures are considered, logarithmic variation is considered as done in the literature [19]. Thermodynamic constants for the considered equilibriums are shown in Table 1.…”
Section: Reaction System Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…When higher temperatures are considered, logarithmic variation is considered as done in the literature [19]. Thermodynamic constants for the considered equilibriums are shown in Table 1.…”
Section: Reaction System Modellingmentioning
confidence: 99%
“…[20] and used by Ref. [19], revealed that new Table 3 for optimized model. Ionic strength of a typical SPL solution is about 3-4 mol kg −1 .…”
Section: Reaction System Modellingmentioning
confidence: 99%
See 3 more Smart Citations